Wage setting in Slovenia: Interpretation of the Wage Dynamics Network (WDN) survey findings in an institutional and macroeconomic context - Biswajit Banerjee; Matija Vodopivec; Urban Sila (IZA Journal of European Labor Studies, 2013)
This paper examines responses to questions on wage setting features in Slovenia's Wage Dynamics Network (WDN) survey in the institutional and macroeconomic context of the Slovene economy. The question on collective wage agreement did not capture the prevailing institutional arrangement of multi-level agreements, and the responses on wage indexation were seemingly at odds with institutional features of wage setting. Labor cost adjustments during the financial crisis were primarily in variable pay components and employment but not in base wages. Minimum wage policy contributed to downward wage rigidity.
Keywords: D22; J31; J38; J50; 330; Wage rigidity; Collective bargaining; Indexation; WDN survey; Slovenia